CRISPR-Cas9 gene-editing tool delivered by cell-penetrating, pH-responsive, core/shell magnetite/silver nanoparticles : an approach for antibiotic resistance spread control in wastewater treatment systems (2020)
Microbial resistance to antibiotics is one of the biggest threats to human health as common infections are becoming harder to treat. As a prevention strategy, reducing the presence of antibiotic-resistant microorganisms (ARMs) in the environment and the dissemination of their genes becomes a matter of great importance. A genetic approach using the CRISPR-Cas9 gene-editing tool arises as a promising alternative to control resistance spread in wastewater treatment plants (WTPs), which have been identified as the main hotspot of dissemination. Vector-mediated gene delivery methods have gained much interest for this purpose, being nanoparticles (NPs) a suitable non-viral alternative. Here, we propose the development and evaluation of core/shell magnetite/silver nanoparticles functionalized with a pH-sensitive polymer (pDMAEMA) with DNA loading and releasing capabilities and conjugated with buforin-II as a cell translocating peptide aider as nanostructured vehicles for bacterial transformation (Buf-pH-MSNPs). Characterization of synthesized NPs via FTIR and TGA confirmed successful conjugations of pDMAEMA and buforin-II. The size of agglomerates in aqueous solution was determined via DLS, while individual particles size in the dry state was determined via SEM and TEM micrographs. A DNA loading and delivery assay showed a high NPs' carrying capacity and delivery efficiency. An antimicrobial activity assay assured high cell viability at low NPs' concentrations. This study shows the efficacy of Buf-pH-MSNPs as gene nanocarriers by achieving a successful transformation of a considerable number of bacterial cells. Future research must be done to determine and improve the NPs' performance under wastewater conditions, evaluate its implementation on scaled-up wastewater treatment systems and its possible impact on natural environments